2001
DOI: 10.1007/s004290000140
|View full text |Cite
|
Sign up to set email alerts
|

Mitoses of existing corticotrophs contribute to their proliferation in the rat pituitary during the late fetal period

Abstract: We studied the proliferation of pituitary corticotrophs quantitatively by labeling the proliferating cells with bromodeoxyuridine (BrdU) and carrying out immunocytochemistry for ACTH in rat fetuses at 19.5 days of gestation. In addition to labeling proliferating cells with a single injection of BrdU, we used double BrdU administrations at 9:00 and 19:00 for a more sensitive detection of proliferating cells. With this double administration, the number of cells labeled with either BrdU or both BrdU and ACTH incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
0
14
1
Order By: Relevance
“…Although several studies supported the usefulness of PCNA as a marker of proliferating cells (Nakane et al 1989;Landberg and Roos 1991;Yamada et al 1992;Nakajima et al 1994;Sasaki et al 1994;Ezaki and Matsuno 1995), some authors pointed out that the expression of PCNA is not restricted to the S phase of the cell cycle and the results obtained should be interpreted with caution (Coltrera and Gown 1991;Connolly and Bogdanffy 1993;Linden et al 1993;Elsasser et al 1994;Atkin et al 1997). Oishi et al (1993) and Taniguchi et al (2001a) applied this method to the proliferation of rat pituitary cells in control adults and in the fetus, showing that PCNA can be used as a sensitive marker of cell proliferation (see below).…”
Section: Methods Used To Detect Cell Mitosismentioning
confidence: 92%
See 2 more Smart Citations
“…Although several studies supported the usefulness of PCNA as a marker of proliferating cells (Nakane et al 1989;Landberg and Roos 1991;Yamada et al 1992;Nakajima et al 1994;Sasaki et al 1994;Ezaki and Matsuno 1995), some authors pointed out that the expression of PCNA is not restricted to the S phase of the cell cycle and the results obtained should be interpreted with caution (Coltrera and Gown 1991;Connolly and Bogdanffy 1993;Linden et al 1993;Elsasser et al 1994;Atkin et al 1997). Oishi et al (1993) and Taniguchi et al (2001a) applied this method to the proliferation of rat pituitary cells in control adults and in the fetus, showing that PCNA can be used as a sensitive marker of cell proliferation (see below).…”
Section: Methods Used To Detect Cell Mitosismentioning
confidence: 92%
“…In an attempt to detect proliferating cells more efficiently, we used BrdU injections twice at an interval of 10 h, or used immunocytochemical detection of PCNA instead of BrdU (Taniguchi et al 2001a), and studied the proliferation at the periods when the percentage of double-labeled cells is at the peak: E19.5 for the ACTH cells and P3-P10 for the other cell types. By these means the BrdU-or PCNA-labeled cells increased 1.3 to 2.0 or 2.4 to 4.5-fold, respectively, compared with the single BrdU injection (Fig.…”
Section: Proliferation Of Rat Pituitary Cells During Ontogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…We have studied, by quantitative immunocytochemistry, the proliferation of corticotrophs and thyrotrophs during late fetal and early postnatal periods, and present data indicating that mitosis contributes considerably to the proliferation of these cell types (Taniguchi et al 2000(Taniguchi et al , 2001a(Taniguchi et al , 2001b. In this study we examined the proliferation and differentiation of somatotrophs and mammotrophs quantitatively by double immunostaining of pituitary sections using anti-bromodeoxyuridine (BrdU), and anti-rat GH or anti-rat PRL.…”
Section: Introductionmentioning
confidence: 98%
“…It was demonstrated that proliferation of corticotrophs was most intensive on day 19 of fetal development (Taniguchi et al 2000(Taniguchi et al , 2001. Dx, as a well-known inhibitor of mitotic activity in various cell types (Kim et al 2004) decreased the rate of division of both immature cells and existing fetal ACTH cells in 19-day-old fetuses.…”
Section: Discussionmentioning
confidence: 98%